Pedagogical Learning Method Strategies in PMDG and Implications for the Development of Educational Innovation - Fachriza, Aries; Mukharom, Rohmah Akhirul; Mustaditami, Anisa Rahma; Velisya, Najwa; Zemzemiyeh (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
Pondok Modern Darussalam Gontor (PMDG) is one of the Pesantren educational institutions that integrates education, discipline, Islamic values, and science. The combination is able to shape the character of the students with Islamic character followed by broad knowledge. This is evidence of the application of teaching art with strategies and techniques that are carried out both indoors and outdoors. The application of the art of teaching is carried out with the principles of the hut and methods in teaching practice and the PMDG patent curriculum taught by the teachers. The teaching approach is combined with traditional and modern methods to keep up with the times. The author conducted this research to get to know more closely the application of the art of teaching pedagogy at Pondok Modern Darussalam Gontor. The education includes: developing critical thinking skills, forming deeper character, and encouraging students to be more independent. The method used by the author is a literature review with a descriptive approach and data collection conducted by the author. The art of pedagogy in Pondok Modern Darussalam Gontor provides learning facilities for students with contextual methods and approaches without any dichotomy between science and religion as a perfect combination.